The Relationship Between Physical Activity Levels and Immune System Resilience in Post-Pandemic Populations - Arif Rahman Hakim; Mahmudah Mahmudah (Universitas Syiah Kuala, 2025)
The COVID-19 pandemic has significantly influenced public health, highlighting the importance of physical activity in maintaining immune system resilience. This study examines the relationship between physical activity levels and immune system resilience in post-pandemic populations using a qualitative approach, specifically a literature review and library research methodology. Various academic sources, including peer-reviewed journals, books, and health reports, were analyzed to explore how different intensities and frequencies of physical activity influence immune system function. The findings indicate that moderate-intensity physical activity enhances immune surveillance, reduces inflammation, and improves overall immune response. Conversely, sedentary behavior and excessive high-intensity exercise may compromise immune function, increasing susceptibility to infections. Furthermore, socio-demographic factors such as age, pre-existing health conditions, and lifestyle choices play a crucial role in determining the effectiveness of physical activity in supporting immune resilience. The study also highlights the need for public health strategies to promote regular physical activity as a preventive measure against immune dysfunction in post-pandemic societies. By synthesizing existing research, this study contributes to a better understanding of how physical activity can be effectively integrated into public health policies to enhance immune resilience. Future research should focus on longitudinal studies to assess the long-term effects of physical activity on immune health in diverse populations. This study underscores the critical role of maintaining an active lifestyle in strengthening immune defense mechanisms, particularly in the context of emerging infectious diseases.